ANALISIS MAQASHID SYARIAH PADA INDEKS PEMBANGUNAN MANUSIA - Irwan Habibi Hasibuan; Hendri Tanjung; Ibdalsyah Ibdalsyah (Univ Ibn Khaldun Bogor, 2019)
This study aims to determine the concept of human development made by UNDP, and its relevance to the condition of the developing country Indonesia at this time , and how the Islamic judge it. In addition , this study also aims to lift Islamic persefektif related human development, as a critique falsifies Human Development Index which is an instrument in determining the countries in the world in the category of developed, developing, undeveloped, or underdeveloped. From the research conducted, it was found that the concept of human development according to the UNDP and maqashid banking is not face to face with each other because both concepts are not mutually contradictory. This can be explained by considering three factors of human development made by UNDP (health, education, income) using Shari'ah maqashid scales consisting of human development in the field of religion, life, intellect, lineage and property. From the results of the comparison can be concluded that part of the maintenance of mental health, education part of the reason maintenance, and maintenance revenue part of the treasure.